2004
DOI: 10.1111/j.1442-2050.2004.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of botulinum toxin injection before pneumatic dilatation in patients with idiopathic achalasia

Abstract: Graded pneumatic dilatation (PD) is an appropriate long-term therapy and botulinum toxin injection (BT) is a relatively short-term therapy in idiopathic achalasia. Their combination has not been previously scrutinized. This study aimed to evaluate the role of BT in enhancing the efficacy of PD with 30 mm balloons. Patients who underwent PD with 30 mm balloons after botulinum toxin injections and a group of age- and sex-matched controls who were treated only with PD were enrolled in the study. Symptom scores we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…One month after dilation, the mean symptom score decreased by 76% in the combined therapy group and by 53% in the control group. Age, sex, duration and severity of symptoms were not correlated with response to treatment [93] . We also conducted a prospective trial.…”
Section: Pneumatic Dilation After Botulinum Toxin Injectionmentioning
confidence: 93%
“…One month after dilation, the mean symptom score decreased by 76% in the combined therapy group and by 53% in the control group. Age, sex, duration and severity of symptoms were not correlated with response to treatment [93] . We also conducted a prospective trial.…”
Section: Pneumatic Dilation After Botulinum Toxin Injectionmentioning
confidence: 93%
“…The treatment with botulinum toxin injection may have a beneficial effect on subsequent pneumatic dilatations and initial data report that response to subsequent dilatations may be enhanced by prior injection with botulinum toxin. 26 The consequence of prior injections of botulinum toxin in patients that subsequently require surgical therapy remains controversial. 27,28 Additionally, botulinum toxin has been used in patients in whom the surgical myotomy or pneumatic dilatation is unsuccessful.…”
Section: Endoscopic Therapymentioning
confidence: 99%
“…However, BT injection can only induce a temporary symptomatic remission in some patients with achalasia. Mikaeli et al [4] reported that treatment with BT was effective only in the short-term and repeated injections were needed to maintain remission. Our study suggested that the response rate to 100 U BT injection decreased from 89.65% at 30 days after the treatment to 55.17% at 1 year after the treatment and, additionally, 13.79% (4/29) patients still had response to BT injection at 2 years after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a single injection of BT wanes over time, without precise explanations. It is possible that the atrophy of postsynaptic nerve ending and muscle, secondary to block of acetylcholine release at presynaptic sites, is reversible [4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation